Positive pole piece, secondary battery and electric device

By using a double-layer structure active layer with 150nm-480nm and 500nm-3000nm particles in the positive electrode sheet, the existing lithium iron phosphate positive electrode sheet materials have strong water absorption and poor kinetic performance due to small particle size and large specific surface area, and a positive electrode sheet with high cohesion and high energy density has been achieved.

CN119852343AActive Publication Date: 2025-04-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202410027211.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-01-08
Publication Date
2025-04-18
Estimated Expiration
2044-01-08

AI Technical Summary

Technical Problem

The existing lithium iron phosphate positive electrode sheet materials have a small particle size and large specific surface area, which leads to strong water absorption, which is prone to side reactions and sticky roller phenomena, affecting the battery capacity and dynamic performance.

Method used

A positive electrode sheet is designed, and a positive electrode active layer with a two-layer structure is adopted. The first active layer contains 150nm-480nm lithium iron phosphate particles, and the second active layer contains 500nm-3000nm lithium iron phosphate particles, through which the cohesion and energy density of the electrode sheet are improved.

Benefits of technology

It effectively improves the cohesion and energy density of the positive electrode sheet, reduces water absorption, avoids powder loss and reduces dynamic performance, and improves the overall performance of the secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852343A_ABST
    Figure CN119852343A_ABST
Patent Text Reader

Abstract

The invention provides a positive pole piece, which comprises a current collector and a positive active layer, the positive active layer is arranged on at least one surface of the current collector, and the positive active layer comprises a first active layer directly coated on the current collector and a second active layer coated on the surface of one side, far away from the current collector, of the first active layer, the first active layer comprises first lithium iron phosphate particles and / or first lithium manganese phosphate particles, the second active layer comprises second lithium iron phosphate particles, and the primary average particle size of the first lithium iron phosphate particles and / or the first lithium manganese phosphate particles is 150-480 nm. And the primary average particle size of the second lithium iron phosphate salt particles is 500-3000 nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a positive electrode sheet, a secondary battery and an electrical device. Background Art

[0002] As a positive electrode material for lithium-ion batteries, lithium iron phosphate has rapidly become a global research hotspot due to its abundant resources, low price, environmental friendliness, and stable voltage in two-phase reactions. The lithium iron phosphate positive active materials used in existing positive electrode plates, such as nano-scale lithium iron phosphate and lithium manganese iron phosphate, have small particle sizes, high specific surface areas, and strong water absorption when in contact with air, so side reactions are prone to occur on the solid-liquid surface. At the same time, during the cold pressing process, it is easy to stick to the roller, stretch, and then lose powder. The actual coating requires a high content of binder, and the high amount of binder actually affects the battery capacity. Summary of the invention

[0003] The present application is made in view of the above-mentioned problem, and its purpose is to provide a positive electrode sheet, a secondary battery and an electric device, wherein the positive electrode sheet has high cohesion, low water absorption and can maintain a high energy density.

[0004] A first aspect of the present application provides a positive electrode plate, comprising a current collector and a positive electrode active layer, wherein the positive electrode active layer is arranged on at least one side of the current collector, the positive electrode active layer comprises a first active layer directly coated on the current collector, and a second active layer coated on the surface of the first active layer away from the current collector, the first active layer comprises first lithium iron phosphate salt particles and / or first lithium manganese iron phosphate salt particles, the second active layer comprises second lithium iron phosphate salt particles, the first lithium iron phosphate salt particles and / or the first lithium manganese iron phosphate salt particles have a primary average particle size of 150nm-480nm, and the second lithium iron phosphate salt particles have a primary average particle size of 500nm-3000nm.

[0005] As described above, the positive electrode plate of the present application is provided with a positive electrode active layer comprising a first active layer and a second active layer, wherein the first active layer comprises lithium iron phosphate salt particles and / or lithium manganese phosphate salt particles (also referred to as "lithium iron (manganese) phosphate salt particles") with a smaller primary average particle size close to the current collector.

[0006] Among them, by making the primary average particle size of the first lithium iron phosphate salt particles and / or the first lithium manganese iron phosphate salt particles and the second lithium iron phosphate salt particles of the embodiment of the present application within the above-mentioned range, the particles of the first active layer and the second active layer can be kept at a suitable micron-level size, thereby avoiding the problems of interfacial side reactions and processing difficulties caused by nano-sizing the particles, and the dynamic performance of the particles will not be reduced due to being limited by an excessively large size.

[0007] In addition, the second active layer contains lithium iron phosphate salt particles with a large primary average particle size away from the current collector. By forming this structure, the positive electrode plate of the embodiment of the present application can improve the cohesion of the surface layer because a layer of large-particle lithium iron phosphate salt particles is arranged on the surface. In addition, since the particle size of the large-particle lithium iron phosphate salt particles is relatively large and the specific surface area is small, the water absorption of the material can be reduced, thereby maintaining the high energy density of the positive electrode plate. In addition, by arranging the large-particle lithium iron phosphate salt particles as the second active layer on the upper layer (the outer surface of the pole piece), it can be ensured that the large-particle lithium iron phosphate salt particles as the second active layer achieve better bonding, the compaction density of the positive electrode plate is improved, and the secondary battery having the positive electrode plate has excellent dynamic performance.

[0008] In any embodiment, the cohesive force of the positive electrode sheet is ≥32 N / m.

[0009] The cohesive force of the positive electrode sheet of the application measured by the measuring method described in the embodiment of the present application is within the above range, thereby avoiding powder loss during the processing of the positive electrode sheet and improving the bonding force between the positive electrode surface and the isolation membrane.

[0010] In any embodiment, the thickness of the first active layer is in the range of 80 μm-140 μm, and optionally 90 μm-120 μm, and the thickness of the second active layer is in the range of 8 μm-50 μm, and optionally 20 μm-35 μm.

[0011] By setting the thickness of each group of the first active layer and the second active layer within the above range, the above technical effect of the present application can be further preferably achieved.

[0012] In any embodiment, the BET specific surface area of ​​the first lithium iron phosphate salt particles and / or the first lithium manganese iron phosphate salt particles is 10 m 2 / g-18m 2 / g, optional 12m 2 / g-16m 2 / g, the BET specific surface area of ​​the second lithium iron phosphate particles is 3m 2 / g-8m 2 / g, optional 4m 2 / g-7m 2 / g.

[0013] By making the BET specific surface areas of the first lithium iron phosphate salt particles and the second lithium iron phosphate salt particles and / or the second lithium manganese iron phosphate salt particles of the embodiment of the present application respectively within the above-mentioned range, it can be beneficial to the stirring of the slurry containing the lithium iron phosphate salt particles and the increase of the solid content, thereby improving the processing problems of the battery cell and further increasing the volume energy density of the battery.

[0014] In any embodiment, the sphericity of the first lithium iron phosphate salt particles and / or the first lithium manganese iron phosphate salt particles is ≤1.3, the sphericity of the second lithium iron phosphate salt particles is ≥1.5, and the first lithium iron phosphate salt particles and / or the first lithium manganese iron phosphate salt particles are closer to a sphere than the second lithium iron phosphate salt particles.

[0015] In this article, the term "sphericity" can be measured by the aspect ratio of the particles. The smaller the aspect ratio, the better the sphericity. The aspect ratio is the ratio of the diameter of the major axis of a primary particle to the diameter of the minor axis. Suppose the diameter in the major axis is a, the diameter in the minor axis is b, and the aspect ratio = a / b. This parameter is often used to describe the morphology of particles and can be used to measure their sphericity. The closer the value is to 1, the higher the sphericity.

[0016] The sphericity can be measured by the method described in the examples of the present application.

[0017] By making the sphericity of the first lithium iron phosphate salt particles and / or the first lithium manganese iron phosphate salt particles and the second lithium iron phosphate salt particles each within the above range, the above technical effect of the present application can be further preferably achieved.

[0018] In any embodiment, the molecular formula of the first lithium iron phosphate salt particle and / or the first lithium manganese iron phosphate salt particle is Li x’ M1 y’ Mn m’ Fe z’ M2 k’ PO4, wherein the M1 includes at least one of Na, K, Ca, Al, Mg or a combination of two or more, the M2 includes one of Ni, Cu, Zn, Ti, Nb, V, Cr and Co or a combination of two or more, 0.95≤x'≤1.15, 0≤y'≤0.1, 0.1≤m'≤0.9, 0.1≤z'≤1, 0≤k'≤0.1, and the content of Mn is ≤1000ppm.

[0019] In the present application, there is no particular limitation on the composition of the first lithium iron phosphate salt particles and / or the first lithium iron manganese phosphate salt particles, and any existing small-particle lithium iron (manganese) phosphate salt particles can be used. For example, in an embodiment of the present application, by using the first lithium iron phosphate salt particles and / or the first lithium iron manganese phosphate salt particles having the above composition, and forming a double-layer structure with the second lithium iron phosphate salt particles in the embodiment of the present application, the above-mentioned effect of the present application can be better achieved.

[0020] In any embodiment, the molecular formula of the second lithium iron phosphate salt particle is Li m Fe x P y Oj Q q , wherein Q includes at least one of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, S, F, Cl, and Br, 0.95≤m≤1.15, 0.9≤x≤1, 0.95≤y≤1, 3.5≤j≤4, and 0<q≤0.1.

[0021] By making the second lithium iron phosphate salt of the embodiment of the present application the above molecular formula and adding one or more of the above elements to modify it, a high-load bulk modification of the second lithium iron phosphate salt particles is achieved, which helps to improve the bulk ion transport capacity of the lithium iron phosphate salt particles and can effectively solve the problem of poor kinetic performance inherent in large particles. In addition, by performing the above modification, the second lithium iron phosphate salt particles can show good kinetic performance when used as a positive electrode material. In the present application, the modification can be specifically manifested as doping and / or coating.

[0022] In any embodiment, the Q includes at least one of Ti, V, Mg, and Nb, and can be Ti. Calculated based on the total weight of the second lithium iron phosphate salt particles, the content of Q is 1000ppm-10000ppm, and can be 2500ppm-6000ppm.

[0023] By doping the lithium iron phosphate salt of the embodiment of the present application with one or more of the above elements and making the content within the above range, it is possible to better achieve the metal bulk modification of the second lithium iron phosphate salt particles while ensuring the primary average particle size of the lithium iron phosphate salt particles, further improve the bulk ion transport capacity of the lithium iron phosphate salt particles, and better solve the problem of poor kinetic performance inherent in large particles.

[0024] In any embodiment, the second lithium iron phosphate salt particles contain carbon, and the carbon content is 1.0 wt %-2.0 wt % based on the total weight of the second lithium iron phosphate salt particles.

[0025] By setting the carbon content of the second lithium iron phosphate salt particles to 0.8 wt %-2.0 wt %, carbon can be coated on the surface of the second lithium iron phosphate salt particles to form a lithium iron phosphate material with a uniform and dense carbon coating layer, greatly improving the conductivity of the particle surface.

[0026] In any embodiment, the first lithium iron phosphate salt particles and / or the first lithium manganese iron phosphate salt particles, and the second lithium iron phosphate salt particles are each independently single crystal particles and / or polycrystalline particles. Optionally, based on the total number of particles of the second lithium iron phosphate salt particles, the number of single crystal particles accounts for more than 90%.

[0027] By using single crystal particles of lithium iron phosphate salt in each active layer of the positive electrode plate of the present application, the phenomenon of polycrystalline particles being crushed and peeling off during the cold pressing process can be effectively avoided, thereby improving the bonding force between the second active layer and the first active layer or the isolation film, thereby improving the dynamic performance and energy density of the positive electrode plate.

[0028] In any embodiment, the capacity proportion η of the second lithium iron phosphate salt particles is ≥88%, and the η is defined as: a battery containing the second lithium iron phosphate salt particles as a positive electrode material is charged and discharged twice at a constant current rate of 0.1C in the voltage range of 2.0V to 3.75V, and then charged and discharged once at a constant current rate of 1C. In the charge and discharge test at the rate of 1C, the capacity value extracted when the discharge voltage is 3.2V is recorded as C1, and the capacity value extracted when the discharge voltage is to 2.0V is C2, η=C1 / C2, wherein the charging process includes constant voltage charging, a constant voltage of 3.75V, and a constant voltage cut-off current of 50uA.

[0029] The capacity ratio η of the second lithium iron phosphate salt particles in the embodiment of the present application is ≥88%, which means that the second lithium iron phosphate salt particles of the present application can enable the secondary battery to show good kinetic performance when used as a positive electrode material.

[0030] In any embodiment, the manufacturing process of the second lithium iron phosphate salt particles includes: providing raw materials containing at least a lithium source, an iron source, a phosphorus source, a carbon source, a carbon film-forming agent, and a modifier, and performing at least two sinterings, wherein the temperature of the first sintering is 500°C-760°C, and can be optionally 550°C-720°C, and the carbon content of the material after the first sintering is 0.01 weight%-0.79 weight%, and can be optionally 0.05 weight%-0.4 weight%; the temperature of the second sintering is 700°C-800°C, and can be optionally 720°C-780°C, and the carbon content of the material after the second sintering is 0.8 weight%-2.0 weight%, and can be optionally 1.0 weight%-1.6 weight%.

[0031] In the preparation process of the second lithium iron phosphate salt particles described in the embodiment of the present application, two sinterings are implemented. Among them, by controlling the temperature of the first sintering within the above range and making the carbon content of the intermediate after sintering within the above range, the lithium iron phosphate precursor obtained after the first sintering can have a larger primary particle size, directly improving the powder compaction and pole piece compaction density of the final product; at the same time, the carbon source added before the first sintering can effectively reduce the trivalent iron in the raw material, improving the purity and stability of the product; by controlling the temperature of the second sintering within the above range and making the carbon content of the sintered material 0.8 wt%-2.0 wt%, carbon can be coated on the surface of the second lithium iron phosphate salt particles, forming a lithium iron phosphate material with a uniform and dense carbon coating layer, greatly improving the surface conductivity of the particles.

[0032] In any embodiment, the first crushing is performed after the first sintering, and the second crushing is performed after the second sintering, wherein the Dv50 of the product after the first crushing is 300nm-1200nm, and can be optionally 400nm-1100nm; the Dv50 of the product after the second crushing is 500nm-5000nm, and can be optionally 700nm-2500nm.

[0033] In the preparation method of the second lithium iron phosphate salt particles of the embodiment of the present application, crushing after two sinterings is implemented. By performing the first crushing after the first sintering, the average particle size of the product is 300nm-1200nm, which can avoid the growth barrier of the carbon material and the modifying element to the crystal, and obtain a micron-level lithium iron phosphate precursor; by performing the second crushing after the second sintering, the average particle size of the product is 500nm-3000nm, and lithium iron phosphate salt particles of the desired particle size can be obtained, and a uniform and dense carbon coating layer can be obtained, which greatly improves the surface conductivity of the particles.

[0034] In any embodiment, the first active layer and the second active layer may also arbitrarily contain a conductive agent, a binder and a dispersant, wherein in the first active layer, the weight ratio of the first lithium iron phosphate salt particles and / or the first lithium manganese iron phosphate salt particles: binder: conductive agent: dispersant is 96-99: 0.5-3: 0.5-3: 0.5-3, which can be optionally 96: 1.0: 2.5: 0.5; in the second active layer, the weight ratio of the second lithium iron phosphate salt particles: binder: conductive agent: dispersant is 96-99: 0.5-3: 0.5-3: 0.5-3, which can be optionally 96.5: 0.5: 2.5: 0.5; the weight ratio of the binder in the first active layer is less than or equal to the weight ratio of the binder in the second active layer.

[0035] In any embodiment, the conductive agent includes any one of natural graphite, artificial graphite, conductive carbon black, carbon fiber, carbon nanotubes, graphene, and conductive polymers or metal powders, or a combination of at least two of them, and conductive carbon black can be selected. The binder includes any one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, or polytetrafluoroethylene, or a combination of at least two of them, and polyvinylidene fluoride can be selected. The dispersant is not particularly limited, as long as it is a dispersant commonly used in the art, including PVP (polyvinyl pyrrolidone) and the like.

[0036] By using the above-mentioned specific conductive agent, binder and dispersant, and making the weight ratio of the first lithium iron phosphate salt particles: binder: conductive agent: dispersant within the above-mentioned range, the positive electrode active layer of the present application can better achieve the above-mentioned effect of the present application.

[0037] The second aspect of the present application provides a secondary battery, comprising the positive electrode sheet described in the first aspect of the present application.

[0038] The third aspect of the present application provides an electrical device, comprising the secondary battery described in the second aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 It is a schematic diagram of the structure of the positive electrode plate of one embodiment of the present application.

[0040] Figure 2 This is an electron microscope image of the positive electrode sheet according to one embodiment of the present application.

[0041] Figure 3 It is a schematic diagram exemplarily showing the particle size of the primary particles of the present application.

[0042] Figure 4 is a schematic diagram of a secondary battery according to one embodiment of the present application.

[0043] Figure 5 yes Figure 4 An exploded view of a secondary battery according to an embodiment of the present application is shown.

[0044] Figure 6 is a schematic diagram of a battery module according to an embodiment of the present application.

[0045] Figure 7 It is a schematic diagram of a battery pack according to one embodiment of the present application.

[0046] Figure 8 yes Figure 7 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0047] Fig. 9 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.

[0048] Description of reference numerals:

[0049] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 cover plate. DETAILED DESCRIPTION

[0050] The following describes in detail the embodiments of the positive electrode sheet, secondary battery and electric device of the present application. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0051] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0052] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0053] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0054] If not otherwise specified, all steps of the present application may be performed sequentially or randomly, and may be performed sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0055] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0056] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0057] The lithium iron phosphate positive active materials used in existing positive electrode plates, such as nano-scale lithium iron phosphate, lithium manganese iron phosphate and other materials, have small particle sizes, high specific surface areas, and strong water absorption. Generally, an active material layer of secondary particles is coated on the surface to improve the surface cohesion of the plate, but the secondary particles will crack and break during cold pressing.

[0058] Based on this, the present application proposes a positive electrode plate, on the surface of which a layer of primary particle material with a larger particle size is designed to be coated to improve the surface cohesion of the electrode plate, thereby avoiding the problem of secondary particles being crushed under pressure, thereby improving the dynamic performance and energy density.

[0059] [Positive electrode]

[0060] The positive electrode plate of the embodiment of the present application includes a current collector and a positive electrode active layer, wherein the positive electrode active layer is arranged on at least one side of the current collector, and the positive electrode active layer includes a first active layer directly coated on the current collector, and a second active layer coated on the surface of the first active layer away from the current collector, the first active layer contains first lithium iron phosphate salt particles and / or first lithium manganese iron phosphate salt particles, the second active layer contains second lithium iron phosphate salt particles, the first lithium iron phosphate salt particles and / or the first lithium manganese iron phosphate salt particles have a primary average particle size of 150nm-480nm, and the second lithium iron phosphate salt particles have a primary average particle size of 500nm-3000nm.

[0061] In some embodiments, the primary average particle size of the first lithium iron phosphate salt particles and / or the first lithium manganese iron phosphate salt particles can be selected as 150nm, 160nm, 170nm, 180nm, 190nm, 200nm, 210nm, 220nm, 230nm, 240nm, 250nm, 260nm, 270nm, 280nm, 290nm, 300nm, 310nm, 320nm, 330nm, 340nm, 350nm, 360nm, 370nm, 380nm, 390nm, 400nm, 410nm, 420nm, 430nm, 440nm, 450nm, 460nm, 470nm or 480nm, or a range between any two of the above values. In some embodiments, the primary average particle size of the second lithium iron phosphate particles may be 500 nm, 600 nm, 650 nm, 700 nm, 790 nm, 800 nm, 870 nm, 900 nm, 920 nm, 1000 nm, 1100 nm, 1200 nm, 1250 nm, 1300 nm, 1400 nm, 1500 nm, 1600 nm, 1700 nm, 1800 nm, 1900 nm, 2000 nm, 2100 nm, 2200 nm, 2300 nm, 2400 nm, 2500 nm, 2600 nm, 2700 nm, 2800 nm, 2900 nm or 3000 nm, or a range between any two of the above values.

[0062] In this article, the term "primary average particle size" refers to the particle size value obtained by statistically analyzing the particle size of particles using the long diameter statistical method under the field of view of a scanning electron microscope. In the particle size statistical process, particles with a primary average particle size less than or equal to 80nm are not included in the statistical range. The primary average particle size of this application is as follows: Figure 3As shown. The primary average particle size refers to the average particle size of primary particles. In this article, "primary particles" refer to particles that do not have obvious agglomeration interfaces in the particle scanning electron microscope image, but may have tiny pores and point or line defects, which are different from powder particles that are the smallest units without structures such as stacking and flocculation. The primary average particle size, the carbon content described later, and the BET specific surface area can be determined using the determination method described in the examples.

[0063] As described above, the positive electrode plate of the present application is provided with a positive electrode active layer comprising a first active layer and a second active layer, wherein the first active layer comprises lithium iron phosphate salt particles and / or lithium manganese phosphate salt particles (also referred to as "lithium iron (manganese) phosphate salt particles") with a smaller primary average particle size close to the current collector.

[0064] Among them, by making the primary average particle size of the first lithium iron phosphate salt particles and / or the first lithium manganese iron phosphate salt particles and the second lithium iron phosphate salt particles of the embodiment of the present application within the above-mentioned range, the particles of the first active layer and the second active layer can be kept at a suitable micron-level size, thereby avoiding the problems of interfacial side reactions and processing difficulties caused by nano-sizing the particles, and the dynamic performance of the particles will not be reduced due to being limited by an excessively large size.

[0065] In addition, the second active layer contains lithium iron phosphate salt particles with a large primary average particle size away from the current collector. By forming this structure, the positive electrode plate of the embodiment of the present application can improve the cohesion of the surface layer because a layer of large-particle lithium iron phosphate salt particles is arranged on the surface. In addition, since the particle size of the large-particle lithium iron phosphate salt particles is relatively large and the specific surface area is small, the water absorption of the material can be reduced, thereby maintaining the high energy density of the positive electrode plate. In addition, by arranging the large-particle lithium iron phosphate salt particles as the second active layer on the upper layer (the outer surface of the pole piece), it can be ensured that the large-particle lithium iron phosphate salt particles as the second active layer achieve better bonding, the compaction density of the positive electrode plate is improved, and the secondary battery having the positive electrode plate has excellent dynamic performance.

[0066] In any embodiment, the cohesive force of the positive electrode sheet is ≥32 N / m.

[0067] The cohesive force of the positive electrode sheet of the application measured by the measuring method described in the embodiment of the present application is within the above range, thereby avoiding powder loss during the processing of the positive electrode sheet and improving the bonding force between the positive electrode surface and the isolation membrane.

[0068] In any embodiment, the thickness of the first active layer is in the range of 80 μm-140 μm, and optionally 90 μm-120 μm, and the thickness of the second active layer is in the range of 8 μm-50 μm, and optionally 20 μm-35 μm.

[0069] In some embodiments, the thickness of the first active layer may be 80 μm, 81 μm, 84 μm, 87 μm, 90 μm, 93 μm, 96 μm, 99 μm, 100 μm, 103 μm, 106 μm, 109 μm, 110 μm, 113 μm, 116 μm, 119 μm, 120 μm, 123 μm, 126 μm, 129 μm, 130 μm, 133 μm, 136 μm, 139 μm or 140 μm, or any range therebetween. In some embodiments, the thickness of the first active layer can be 8 μm, 11 μm, 14 μm, 17 μm, 19 μm, 21 μm, 24 μm, 27 μm, 30 μm, 34 μm, 37 μm, 40 μm, 43 μm, 46 μm, 49 μm or 50 μm, or a range between any two of the above values.

[0070] By setting the thickness of each group of the first active layer and the second active layer within the above range, the above technical effect of the present application can be further preferably achieved.

[0071] In any embodiment, the BET specific surface area of ​​the first lithium iron phosphate salt particles and / or the first lithium manganese iron phosphate salt particles is 10 m 2 / g-18m 2 / g, optional 12m 2 / g-16m 2 / g, the BET specific surface area of ​​the second lithium iron phosphate particles is 3m 2 / g-8m 2 / g, optional 4m 2 / g-7m 2 / g.

[0072] In some embodiments, the BET specific surface area of ​​the first lithium iron phosphate salt particles and / or the first lithium manganese iron phosphate salt particles can be 10 m 2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g, 16m 2 / g, 17m 2 / g or 8m 2 In some embodiments, the BET specific surface area of ​​the second lithium iron phosphate particles can be 3 m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g or 8m 2 / g, or the range between any two of the above values. The BET specific surface area can be measured using the measurement method described in the examples.

[0073] By making the BET specific surface areas of the first lithium iron phosphate salt particles and the second lithium iron phosphate salt particles and / or the second lithium manganese iron phosphate salt particles of the embodiment of the present application respectively within the above-mentioned range, it can be beneficial to the stirring of the slurry containing the lithium iron phosphate salt particles and the increase of the solid content, thereby improving the processing problems of the battery cell and further increasing the volume energy density of the battery.

[0074] In any embodiment, the sphericity of the first lithium iron phosphate salt particles and / or the first lithium iron manganese phosphate salt particles is ≤1.3, and that of the second lithium iron phosphate salt particles is ≥1.5, and the sphericity of the first lithium iron phosphate salt particles and / or the first lithium iron manganese phosphate salt particles is higher than the sphericity of the second lithium iron phosphate salt particles.

[0075] In this article, the term "sphericity" can be measured by the aspect ratio of the particles. The smaller the aspect ratio, the better the sphericity. The aspect ratio is the ratio of the diameter of the major axis of a primary particle to the diameter of the minor axis. Suppose the diameter in the major axis is a, the diameter in the minor axis is b, and the aspect ratio = a / b. This parameter is often used to describe the morphology of particles and can be used to measure their sphericity.

[0076] The sphericity can be measured by the method described in the examples of the present application.

[0077] By making the sphericity of the first lithium iron phosphate salt particles and / or the first lithium manganese iron phosphate salt particles and the second lithium iron phosphate salt particles each within the above range, the above technical effect of the present application can be further preferably achieved.

[0078] [First lithium iron phosphate salt particles and / or first lithium manganese iron phosphate salt particles]

[0079] In any embodiment, the molecular formula of the first lithium iron phosphate salt particle and / or the first lithium manganese iron phosphate salt particle is Li x’ M1 y’ Mn m’ Fe z’ M2 k’ PO4, wherein the M1 includes at least one of Na, K, Ca, Al, Mg or a combination of two or more, the M2 includes one of Ni, Cu, Zn, Ti, Nb, V, Cr and Co or a combination of two or more, 0.95≤x'≤1.15, 0≤y'≤0.1, 0.1≤m'≤0.9, 0.1≤z'≤1, 0≤k'≤0.1, and the content of Mn is ≤1000ppm.

[0080] In the present application, there is no particular limitation on the composition of the first lithium iron phosphate salt particles and / or the first lithium iron manganese phosphate salt particles, and any existing small-particle lithium iron (manganese) phosphate salt particles can be used. For example, in an embodiment of the present application, by using the first lithium iron phosphate salt particles and / or the first lithium iron manganese phosphate salt particles having the above composition, and forming a double-layer structure with the second lithium iron phosphate salt particles in the embodiment of the present application, the above-mentioned effect of the present application can be better achieved.

[0081] [Second lithium iron phosphate salt particles]

[0082] The primary average particle size of the second lithium iron phosphate salt particles in the embodiment of the present application is 500nm to 3000nm, and can be 650nm to 2500nm, and the BET specific surface area is 3m 2 / g~8m 2 / g, optional 4m 2 / g~7m 2 / g, calculated based on the total weight of the second lithium iron phosphate salt particles, the carbon content of the second lithium iron phosphate salt particles is Cx weight %, wherein 0.8≤Cx≤2.0, optionally 1.0≤Cx≤1.6, and the ratio z of the BET specific surface area to Cx satisfies 1.5≤z≤8.5, optionally 3≤z≤6.

[0083] By making the primary average particle size of the second lithium iron phosphate particles of the embodiment of the present application 500nm to 3000nm and the BET specific surface area 3m 2 / g~8m 2 / g, the carbon content calculated based on the total weight of the second lithium iron phosphate salt particles is Cx weight % (0.8≤Cx≤2.0), and at the same time, the ratio z of the BET specific surface area of ​​the second lithium iron phosphate salt particles to Cx (i.e., BET specific surface area / Cx) satisfies the range of 1.5≤z≤8.5, which can improve the dynamic properties of the second lithium iron phosphate salt particles with an average particle size within the above range; the particles are kept in a suitable micron-level size, thereby avoiding the interface side reactions and processing difficulties caused by nano-sizing the particles, and the particles will not be limited by the excessive size and thus reduce the dynamic properties; in addition, it is beneficial to the stirring of the slurry containing the second lithium iron phosphate salt particles and the increase of the solid content, thereby improving the processing problem of the battery cell, and then increasing the volume energy density of the battery; in addition, it can avoid affecting the normal deintercalation of lithium ions due to the excessively high density of the carbon coating, thereby affecting the performance of the battery cell capacity.

[0084] Compared with the prior art, the second lithium iron phosphate salt particles in the embodiment of the present application have a smaller specific surface area when containing the same carbon content, which means that the particles contain less floating carbon, which can make the carbon contained in the second lithium iron phosphate salt particles more uniform and dense and each particle is coated, thereby improving the surface conductivity of the particles and improving their kinetic performance as a positive electrode material.

[0085] In any embodiment, the second lithium iron phosphate salt has a molecular formula Li m Fe x P y O j Q q , wherein Q includes at least one of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, Si, N, S, F, Cl, and Br, 0.95≤m≤1.15, 0.9≤x≤1, 0.95≤y≤1, 3.5≤j≤4, and 0<q≤0.1.

[0086] By making the second lithium iron phosphate salt of the embodiment of the present application the above molecular formula and adding one or more of the above elements to modify it, a high-load bulk modification of the second lithium iron phosphate salt particles is achieved, which helps to improve the bulk ion transport capacity of the second lithium iron phosphate salt particles and can effectively solve the problem of poor kinetic performance inherent in large particles. In addition, by performing the above modification, the second lithium iron phosphate salt particles can show good kinetic performance when used as a positive electrode material. In the present application, the modification can be specifically manifested as doping and / or coating.

[0087] In any embodiment, the Q includes at least one of Ti, V, Mg, and Nb, and can be Ti. The content of Q is 1000ppm-10000ppm, and can be 2500ppm-6000ppm, calculated based on the total weight of the second lithium iron phosphate salt particles. In some embodiments, the content of Ti, V, Mg and / or Nb can be 2500ppm, 2600ppm, 2700ppm, 2800ppm, 2900ppm, 3000ppm, 3100ppm, 3200ppm, 3300ppm, 3400ppm, 3500ppm, 3600ppm, 3700ppm, 3800ppm, 3900ppm, 4000ppm, 5000ppm, 5100ppm, 5200ppm, 5300ppm, 5400ppm, 5500ppm, 5600ppm, 5700ppm, 5800ppm, 5900ppm, 6000ppm, 6100ppm, 6100ppm, 6200ppm, 6300ppm, 6400ppm, 6500ppm, 6600ppm, 6700ppm, 6800ppm, 6900ppm, 700ppm, 7100ppm, 7200ppm, 7300ppm, 7400ppm, 7500ppm, 7600ppm, 7700ppm, 7800ppm, 7900ppm, 800ppm, 8100ppm, 8100ppm, 8200ppm, 8300ppm, 8400ppm, 8500ppm, 8600ppm, 8700ppm, 8800ppm, 8900ppm, 900ppm, 91 m, 4100ppm, 4200ppm, 4300ppm, 4400ppm, 4500ppm, 4600ppm, 4700ppm, 4800ppm, 4900ppm, 5000ppm, 5100ppm, 5200ppm, 5300ppm, 5400ppm, 5500ppm, 5600ppm, 5700ppm, 5800ppm, 5900ppm or 6000ppm, or a range between any two of the above values.

[0088] By adding one or more of the above elements to the second lithium iron phosphate salt in the embodiment of the present application and making the content within the above range, it is possible to better achieve the metal bulk modification of the second lithium iron phosphate salt particles while ensuring the primary average particle size of the second lithium iron phosphate salt particles, further improve the bulk ion transport capacity of the second lithium iron phosphate salt particles, and better solve the problem of poor kinetic properties inherent in large particles.

[0089] In any embodiment, the second lithium iron phosphate salt particles contain carbon, and the carbon content is 1.0 wt %-2.0 wt % based on the total weight of the second lithium iron phosphate salt particles.

[0090] In the second lithium iron phosphate salt particles of the embodiment of the present application, the carbon may exist in a state of being mixed with the second lithium iron phosphate salt particles, or in a state of being coated on the second lithium iron phosphate salt particles. The carbon in the second lithium iron phosphate salt particles may be coated on the second lithium iron phosphate salt particles, thereby enabling the carbon to form a uniform and dense carbon coating layer on the surface of the second lithium iron phosphate salt particles, thereby improving the conductivity of the particle surface.

[0091] In any embodiment, the capacity proportion η of the second lithium iron phosphate salt particles is ≥88%, and the η is defined as: a battery containing the second lithium iron phosphate salt particles as a positive electrode material is charged and discharged twice at a constant current rate of 0.1C in the voltage range of 2.0V to 3.75V, and then charged and discharged once at a constant current rate of 1C. In the charge and discharge test at the rate of 1C, the capacity value at the discharge voltage of 3.2V is extracted and recorded as C1, and the capacity value at the discharge voltage to 2.0V is extracted as C2, η=C1 / C2, wherein the charging process includes constant voltage charging, a constant voltage of 3.75V, and a constant voltage cut-off current of 50uA.

[0092] η represents the platform retention performance of the material, and this value is strongly correlated with the discharge power performance of the battery. When this value is large, the battery can still maintain good power performance when it is discharged to a low SOC (battery state of charge), that is, the voltage drop value of the battery is small when the battery is discharged at a high current at a low power level. The capacity proportion η of the second lithium iron phosphate salt particles in the embodiment of the present application is ≥88%, indicating that the second lithium iron phosphate salt particles of the present application can enable the secondary battery to show good kinetic performance when used as a positive electrode material.

[0093] In any embodiment, the second lithium iron phosphate salt particles satisfy at least one of the following a)-f):

[0094] a) Dv10 of the second lithium iron phosphate salt particles is ≥ 0.2 μm;

[0095] b) the Dv50 of the second lithium iron phosphate salt particles is 0.5-5 μm;

[0096] c) Dv90 of the second lithium iron phosphate salt particles is ≤8 μm;

[0097] d) Dv99 of the second lithium iron phosphate salt particles is ≤10 μm;

[0098] e) The powder compaction density of the second lithium iron phosphate salt under a pressure of 3T is ≥ 2.25 g / cm 3 ;

[0099] f) The powder resistivity of the second lithium iron phosphate salt is less than 60Ω·cm.

[0100] In this application, the above Dv10, Dv90, and Dv99 refer to the particle sizes corresponding to the volume cumulative particle size distribution percentages in the particles reaching 10%, 90%, and 99%, respectively. The test method is the same as that of the above Dv50, and the standard in the examples of this application can be used for determination.

[0101] It should be noted that the Dv10 is a large index, so no upper limit can be given, and the Dv90 is a small index, so no lower limit can be given.

[0102] By making the second lithium iron phosphate salt particles satisfy at least one of a) to f), the second lithium iron phosphate salt particles can achieve the above technical effects better.

[0103] In the present application, the test method of the powder resistivity is: refer to the national standard GB / T33822-2017, use a powder resistivity meter (Suzhou Jinglattice, ST2722 model), weigh 1g of sample (error within ±0.005g) and add it to the feeding chamber, apply a pressure of 8MPa, test the forward resistivity and reverse resistivity of the sample respectively, and take the average of the two as the powder resistivity of the sample.

[0104] In this application, the compacted density of the powder is defined as: during the external force compression process, as the powder moves and deforms, larger gaps are filled, the contact area between particles increases, the attraction between atoms is generated, and the mechanical fit between particles is enhanced, thus forming a compact with a certain density and strength, the unit is g / cm 3 .

[0105] The compaction density test method is as follows: referring to the national standard GB / T 24533-2009, a certain amount of powder is placed on a compaction mold, and a metal disc is placed on the upper and lower parts of the mold. The powder is placed between the metal discs, a metal cylinder is placed on the top, and the mold is placed on a compaction density instrument. Different pressures are set, and the thickness of the powder under different pressures can be read on the device. The compaction density is calculated by ρ=m / v.

[0106] According to the following powder compaction density calculation results, ρc=m / V=m / (S×H); where ρc is the powder compaction density (g / cm 3 ), m is the mass of the material (g), S is the bottom area of ​​the mold (1.327cm 2 ), H is the height of the sample after compaction (cm).

[0107] In some embodiments, the carbon content of the second lithium iron phosphate salt particles may be 0.8 wt%, 0.9 wt%, 1 wt%, 1.1%, 1.2 wt%, 1.3 wt%, 1.4 wt%, 1.5 wt%, 1.6 wt%, 1.7 wt%, 1.8 wt%, 1.9 wt% or 2.0 wt%, or a range between any two of the above values.

[0108] By setting the carbon content of the second lithium iron phosphate salt particles to 0.8 wt %-2.0 wt %, carbon can be coated on the surface of the second lithium iron phosphate salt particles to form a lithium iron phosphate material with a uniform and dense carbon coating layer, greatly improving the conductivity of the particle surface.

[0109] In the lithium iron phosphate salt particles of the embodiment of the present application, the carbon may exist in a state of being mixed with the second lithium iron phosphate salt particles, or in a state of being coated on the second lithium iron phosphate salt particles. The carbon in the second lithium iron phosphate salt particles may be coated on the second lithium iron phosphate salt particles, thereby enabling the carbon to form a uniform and dense carbon coating layer on the surface of the second lithium iron phosphate salt particles, thereby improving the conductivity of the particle surface.

[0110] In any embodiment, the second iron-lithium salt particles are single crystal particles and / or polycrystalline particles. Optionally, based on the total number of particles of the second iron-lithium salt particles, the number of single crystal particles accounts for more than 90%.

[0111] By using the above-mentioned proportion of single crystal particles of lithium iron phosphate salt in each active layer of the positive electrode plate of the present application, the phenomenon of polycrystalline particles being crushed and peeling off during the cold pressing process can be effectively avoided, thereby improving the bonding force between the second active layer and the first active layer or the isolation film, thereby improving the dynamic performance and energy density of the positive electrode plate.

[0112] [Preparation method of the second lithium iron phosphate salt particles]

[0113] In any embodiment, the manufacturing process of the second lithium iron phosphate salt particles includes: providing raw materials containing at least a lithium source, an iron source, a phosphorus source, a carbon source, a carbon film-forming agent, and a modifier, and performing at least two sinterings, wherein the temperature of the first sintering is 500°C-760°C, and can be optionally 550°C-720°C, and the carbon content of the material after the first sintering is 0.01 weight%-0.79 weight%, and can be optionally 0.05 weight%-0.4 weight%; the temperature of the second sintering is 700°C-800°C, and can be optionally 720°C-780°C, and the carbon content of the material after the second sintering is 0.8 weight%-2.0 weight%, and can be optionally 1.0 weight%-1.6 weight%.

[0114] In some embodiments, the temperature of the first sintering may be 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C or 760°C, or a range between any two of the above values. The temperature of the second sintering may be 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C or 800°C, or a range between any two of the above values. The carbon content of the material after the first sintering can be selected to be 0.01 weight%, 0.05 weight%, 0.10 weight%, 0.15 weight%, 0.2 weight%, 0.25 weight%, 0.3 weight%, 0.35 weight%, 0.4 weight%, 0.45 weight%, 0.5 weight%, 0.55 weight%, 0.6 weight%, 0.65 weight%, 0.7 weight%, 0.75 weight%, 0.79 weight%; the carbon content of the material after the second sintering is 0.8 weight%-2.0 weight%, which can be selected as 0.8 weight%, 0.9 weight%, 1 weight%, 1.1%, 1.2 weight%, 1.3 weight%, 1.4 weight%, 1.5 weight%, 1.6 weight%, 1.7 weight%, 1.8 weight%, 1.9 weight% or 2.0 weight%, or a range between any two of the above values.

[0115] In the preparation process of the second lithium iron phosphate salt particles of the embodiment of the present application, two sinterings are implemented. Among them, by controlling the temperature of the first sintering within the above range and making the carbon content of the intermediate after sintering within the above range, the lithium iron phosphate precursor obtained after the first sintering can have a larger particle size, which directly improves the powder compaction of the final product and the compaction density of the pole piece. In addition, by adding a lower content of carbon source during the first sintering, the barrier effect of the carbon layer on the growth process of the lithium iron phosphate particles is greatly reduced, which is conducive to the crystal growth of the particles at a lower temperature, and is also conducive to the solid-phase diffusion reaction between the modifier and the lithium iron phosphate material, thereby achieving a higher concentration of metal ion doping. Compared with the traditional method of using high temperature to achieve particle growth, the above-mentioned preparation method of the present application can first synthesize large particles at a lower temperature, which can improve the phenomenon of cracking of the carbon layer on the surface of the particles at high temperature and improve the density of the surface carbon; at the same time, during the first sintering process, the carbon source can effectively reduce the trivalent iron in the raw material, thereby improving the purity and stability of the product; by controlling the temperature of the second sintering within the above range and making the carbon content of the sintered material 0.8 weight%-2.0 weight%, carbon can be coated on the surface of the second iron lithium salt particles to form a lithium iron phosphate material with a uniform and dense carbon coating layer, thereby greatly improving the surface conductivity of the particles.

[0116] In any embodiment, the first crushing is performed after the first sintering, and the second crushing is performed after the second sintering, wherein the Dv50 of the product after the first crushing is 300nm-1200nm, and can be optionally 400nm-1100nm; the Dv50 of the product after the second crushing is 500nm-5000nm, and can be optionally 700nm-2500nm.

[0117] In some embodiments, the Dv50 of the product after the first pulverization is 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, 1100 nm, or 1200 nm, or a range between any two of the above values. In some embodiments, the Dv50 of the product after the second crushing is 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, 1500nm, 1600nm, 1700nm, 1800nm, 1900nm, 2000nm, 2300nm, 2500nm, 2700nm, 3000nm, 3300nm, 3500nm, 3700nm, 4000nm, 4300nm, 4500nm, 4700nm, 5000nm, or a range between any two of the above values.

[0118] Herein, the term "Dv50" refers to the particle size corresponding to when the volume cumulative particle size distribution percentage in the particles reaches 50%. The determination of Dv50 can be carried out using the determination method described in the examples.

[0119] In the preparation method of the second lithium iron salt particles of the embodiment of the present application, crushing after two sinterings is implemented. By performing the first crushing after the first sintering, the average particle size of the product is 300nm-1200nm, which can avoid the growth barrier of the crystal by the carbon material and the modifying element, and obtain a micron-level lithium iron phosphate precursor; by performing the second crushing after the second sintering, the average particle size of the product is 500nm-5000nm, and lithium iron phosphate particles of the desired particle size can be obtained, and a uniform and dense carbon coating layer can be obtained, which greatly improves the surface conductivity of the particles.

[0120] In any embodiment, the first active layer and the second active layer may also arbitrarily contain a conductive agent, a binder and a dispersant, wherein in the first active layer, the weight ratio of the first lithium iron phosphate salt particles and / or the first lithium manganese iron phosphate salt particles: binder: conductive agent: dispersant is 96-99: 0.5-3: 0.5-3: 0.5-3, which can be optionally 96: 1.0: 2.5: 0.5; in the second active layer, the weight ratio of the second lithium iron phosphate salt particles: binder: conductive agent: dispersant is 96-99: 0.5-3: 0.5-3: 0.5-3, which can be optionally 96.5: 0.5: 2.5: 0.5; the weight ratio of the binder in the first active layer is less than or equal to the weight ratio of the binder in the second active layer.

[0121] In any embodiment, the conductive agent includes any one or a combination of at least two of natural graphite, artificial graphite, conductive carbon black, carbon fiber, carbon nanotubes, graphene, and conductive polymers or metal powders, and conductive carbon black can be selected. The binder includes any one or a combination of at least two of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, or polytetrafluoroethylene, and polyvinylidene fluoride can be selected.

[0122] By using the above-mentioned specific conductive agent, binder and dispersant, and making the weight ratio of the first lithium iron phosphate salt particles: binder: conductive agent: dispersant within the above-mentioned range, the positive electrode active layer of the present application can better achieve the above-mentioned effect of the present application.

[0123] In any embodiment, the preparation method of the second iron lithium salt particles includes: providing at least a lithium source, an iron source, a phosphorus source, a carbon source, a modifier, and a carbon film-forming agent as raw materials, wherein the mixing ratio of the lithium source, the iron source, and the phosphorus source, calculated on the basis of the atomic molar number of each element, satisfies Fe:P=0.96-0.985, Li:Fe=1.0-1.1:0.95-1.1; the carbon source and the carbon film-forming agent, calculated on the basis of the weight ratio, satisfy the carbon source:carbon film-forming agent=9:1-2:8.

[0124] In some embodiments, the mixing ratio of the iron source and the phosphorus source, calculated on the basis of the atomic moles of each element, satisfies Fe:P=0.96:1, Fe:P=0.965:1, Fe:P=0.97:1, Fe:P=0.975:1, Fe:P=0.98:1 or Fe:P=0.985:1.

[0125] In some embodiments, the mixing ratio of the lithium source to the iron source, calculated on the basis of the atomic moles of each element, satisfies Li:Fe=1.0:1.1, Li:Fe=0.99:1.1, Li:Fe=0.98:1.1, Li:Fe=0.97:1.1, Li:Fe=0.96:1.1 or Li:Fe=0.95:1.1.

[0126] In some embodiments, the weight ratio of the carbon source to the carbon film-forming agent may be 9:1, 8:2, 7:3, 6:4, 5:5, 4:6, 3:7 or 2:8.

[0127] By using raw materials containing a lithium source, an iron source, a phosphorus source, a carbon source, a modifier, and a carbon film-forming agent in the above-mentioned proportions, the primary average particle size, carbon content, BET specific surface area, and z value of the second lithium iron phosphate salt particles of the first aspect of this application can be well formed. Specifically, as described above, by making the primary average particle size of the second lithium iron phosphate salt particles of the embodiment of the present application 500nm to 3000nm, the particles can be kept at a suitable micron-level size, thereby avoiding the problems of interfacial side reactions and processing difficulties caused by nano-sizing the particles, and the particles will not be limited by excessive size and the dynamic performance will not be reduced. In addition, by making the BET specific surface area of ​​the second lithium iron phosphate salt particles of the embodiment of the present application 3m 2 / g~8m 2 / g, which can be beneficial to the stirring of the slurry containing the lithium iron phosphate salt particles and the increase of the solid content, thereby improving the processing problem of the battery core, and further increasing the volume energy density of the battery. In addition, by making the ratio z of the BET specific surface area of ​​the second lithium iron phosphate salt particles of the embodiment of the present application to Cx satisfy the range of 1.5≤z≤8.5, the carbon contained in the second lithium iron phosphate salt particles can be made more uniform and dense, thereby improving the surface conductivity of the particles.

[0128] In any embodiment, in the preparation method of the second iron lithium salt particles, the lithium source is a lithium compound, including one or more of lithium dihydrogen phosphate, lithium oxalate, lithium carbonate, lithium oxide, lithium hydroxide and lithium acetate, and lithium carbonate can be selected; the iron source is an iron compound, including at least one of ferric hydroxide, ferrous chloride, ferric oxide, ferric phosphate, ferric pyrophosphate, ferrous oxalate, iron powder, ferric nitrate, ferric oxide and ferric hydroxide, and ferric oxide can be selected; the phosphorus source is a phosphoric acid compound, including phosphoric acid, dihydrogen phosphate, The present invention relates to a novel carbon-containing material comprising one or more of ammonium and diammonium hydrogen phosphate, which can be phosphoric acid; the modifier comprises at least one of titanium dioxide, vanadium pentoxide, n-butyl titanate, ammonium metavanadate, niobium ethanol, niobium oxalate, niobium pentoxide, magnesium hydroxide and magnesium nitrate, which can be titanium dioxide; the carbon source comprises at least one of citric acid, glucose, sucrose, starch, fructose and lactose, which can be glucose; the carbon film-forming agent comprises one or more of polyethylene glycol, polyaniline, polyacrylonitrile, polyvinyl pyrrolidone and polyvinyl alcohol, which can be polyaniline.

[0129] By selecting the above substances as the lithium source, iron source, phosphorus source, modifier, carbon source and carbon film-forming agent respectively used in the preparation method of the second lithium iron phosphate salt particles of the embodiment of the present application, the primary average particle size, carbon content, BET specific surface area and z value of the second lithium iron phosphate salt particles of the embodiment of the present application can be well formed. Thereby, the large particle size of the second lithium iron phosphate salt particles of the embodiment of the present application is better achieved, and at the same time, excellent kinetic performance is achieved when it is used as a positive electrode material.

[0130] In any embodiment, the heating rates in the first sintering and the second sintering are independently 2°C / min-20°C / min, the first sintering constant temperature time is 1h-6h; and the second sintering constant temperature time is 2h-12h.

[0131] In some embodiments, the heating rates in the first sintering and the second sintering are each independently 2°C / min, 5°C / min, 7°C / min, 10°C / min, 13°C / min, 15°C / min, 17°C / min or 20°C / min.

[0132] In some embodiments, the constant temperature sintering time of the first sintering is 1 hour to 6 hours. In some embodiments, the constant temperature sintering time of the first sintering can be selected as 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours.

[0133] In some embodiments, the constant temperature sintering time of the second sintering is 2h-12h. In some embodiments, the constant temperature sintering time of the second sintering can be selected as 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h, 10h, 10.5h, 11h, 11.5h or 12h.

[0134] By controlling the heating rate and the constant temperature time in the first sintering and the second sintering within the above range, it is possible to prevent excessive side reactions during the sintering process due to too fast a heating, thereby affecting the primary average particle size, carbon content, BET specific surface area and z value of the obtained second lithium iron phosphate salt particles. In this way, the large particle size of the second lithium iron phosphate salt particles of the embodiment of the present application is better achieved, and at the same time, excellent kinetic performance is achieved when it is used as a positive electrode material.

[0135] In any embodiment, after the first sintering and before the second sintering, the product after the first sintering is carbon coated, and the amount of the carbon coating is 0.01-1.99%, and can be 0.2-1.5%. Specifically, it can be 0.2 wt%-1.6 wt%, and specifically, it can be 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt%, 1.0 wt%, 1.1 wt%, 1.2 wt%, 1.3 wt%, 1.4 wt%, 1.5 wt% or 1.6 wt%, or the range between any two of the above values.

[0136] By coating the product after the first sintering with carbon within the above-mentioned content range after the first sintering and before the second sintering, a uniform and dense carbon coating layer can be formed on the surface of the lithium iron phosphate salt particles during the second sintering process.

[0137] In any embodiment, the carbon coating is performed by vapor deposition during sintering, or by carbonizing and coating the carbon source at high temperature.

[0138] In the preparation method of the second lithium iron phosphate salt particles of the embodiment of the present invention, the implementation method of the carbon coating is not particularly limited, and the second lithium iron phosphate salt particles can be carbon-coated by vapor deposition, thereby forming a uniform and dense carbon coating layer on the surface of the second lithium iron phosphate salt particles. In any embodiment, after the first sintering and the second sintering, the sintered product is crushed, and the crushing can be selected from one or more of mechanical crushing, sand milling, and air flow crushing.

[0139] In the method for preparing the second lithium iron phosphate salt particles according to the embodiment of the present invention, the pulverization method is not particularly limited. By adopting the above-mentioned specific pulverization method, it is advantageous to obtain a desired primary average particle size.

[0140] In the method for preparing the second lithium iron phosphate salt particles according to the embodiment of the present invention, the pulverization method is not particularly limited. By adopting the above-mentioned specific pulverization method, it is advantageous to obtain a desired primary average particle size.

[0141] [current collector]

[0142] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, aluminum foil may be used. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming aluminum foil on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0143] [Negative electrode]

[0144] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0145] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0146] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0147] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0148] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0149] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0150] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0151] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0152] [Electrolytes]

[0153] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0154] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0155] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0156] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0157] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0158] [Isolation film]

[0159] In some embodiments, the secondary battery includes a separator. The present application has no particular limitation on the type of separator, and any known porous structure separator with good chemical stability and mechanical stability can be selected.

[0160] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0161] [Secondary battery]

[0162] In one embodiment of the present application, a secondary battery is provided, which includes the positive electrode plate.

[0163] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0164] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0165] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0166] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0167] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 4 The secondary battery 5 is a square structure as an example.

[0168] In some embodiments, reference Figure 5 , the outer package may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0169] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0170] Figure 6 4 is an example of a battery module. Figure 6 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0171] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0172] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0173] Figure 7 and Figure 81 is a battery pack 1 as an example. Figure 7 and Figure 8 The battery pack 1 may include a battery box and a plurality of battery modules 6 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0174] [Electrical devices]

[0175] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0176] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.

[0177] Fig. 9 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.

[0178] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.

[0179] Example

[0180] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0181] Example 1

[0182] 1. Preparation of lithium iron phosphate particles

[0183] 1) Preparation of the second lithium iron phosphate salt particles

[0184] Weigh lithium carbonate, ferric oxide, phosphoric acid, glucose, titanium dioxide (based on the total weight of lithium iron phosphate particles, the amount of titanium dioxide added is such that the titanium content in the prepared lithium iron phosphate particles is 5000ppm) and polyaniline, wherein the weight ratios of Li element, Fe element and P element are such that Fe:P=0.968:1, Li:Fe=1:0.98, and the weight ratio of glucose to polyaniline is such that glucose:polyaniline=1:2. The amount of glucose added is such that after the first sintering is completed, the carbon content accounts for 0.15% of the weight of the lithium iron phosphate precursor. Add water to the above substances to obtain a mixture slurry.

[0185] Use a ball mill to mix the mixture slurry evenly, grind it with a sand mill to obtain a slurry with a solid content of 38% and a Dv50 of 0.40μm, and spray dry it (the negative pressure of the high-speed spray dryer is -650~-200Pa, the inlet temperature is 300℃~360℃, and the outlet temperature is 100℃~140℃). The dried reactants are loaded into a sintering furnace for the first sintering, and the heating rate is controlled at 5℃ / min, the insulation temperature is controlled at 650℃, and the insulation time is 4h. After the material is cooled, it is crushed by a mechanical mill to obtain a powder.

[0186] Add glucose as a carbon source and polyaniline as a carbon film-forming agent to the obtained powder, and then mix with water to obtain a material with a solid content of 40%. Among them, the amount of glucose and polyaniline added satisfies that the carbon content of the product after the second sintering is 1.2% (based on the total weight of the lithium iron phosphate salt particles), and the weight ratio of glucose to polyaniline satisfies glucose: polyaniline = 1:2. The above materials are processed by ball milling and sand milling to obtain a slurry, and the Dv50 of the insoluble matter in the slurry is 550nm. Spray drying (the negative pressure of the high-speed spray dryer is -650 to -200Pa, the inlet temperature is 300℃ to 360℃, and the outlet temperature is 100℃ to 140℃). The dried reactants are loaded into a sintering furnace for a second low-temperature sintering (the heating rate is controlled at 5℃ / min, the sintering temperature is 750℃, and the sintering time is 4h). After the material is cooled, it is crushed for the second time to an average particle size of 870 nm. After demagnetization, lithium iron phosphate salt particles are obtained, with a carbon content of 1.2% and a Ti content of 5000 ppm in the lithium iron phosphate salt particles.

[0187] 2) Preparation of the first lithium iron phosphate salt particles

[0188] The first lithium iron phosphate salt particles used in this application are commercially available products purchased from Guangdong Brunp Recycling Technology Co., Ltd. with the item number BP-LFP-101; the second lithium manganese iron phosphate salt particles used in this application were purchased from Guangdong Brunp Recycling Technology Co., Ltd. with the item number BP-115.

[0189] 2. Preparation of active layer slurry

[0190] 1) Preparation of the first active layer slurry

[0191] The first lithium iron phosphate salt particles, conductive carbon black as a conductive agent, polyvinylidene fluoride as a binder, and PVP (polyvinyl pyrrolidone) as a dispersant are mixed in a mass percentage of 96.0:2.5:1.0:0.5, and a certain amount of N-methylpyrrolidone is added to mix and stir evenly, and disperse to prepare a first active layer positive electrode slurry. The BET specific surface area of ​​the first lithium iron phosphate salt particles is greater than the BET specific surface area of ​​the second lithium iron phosphate salt particles, and the first lithium iron phosphate salt particles have an average primary particle size of 360nm and a Dv50 of 1.0μm.

[0192] 2) Preparation of the second active layer slurry

[0193] The second lithium iron phosphate salt particles, conductive carbon black as a conductive agent, polyvinylidene fluoride as a binder, and PVP (polyvinyl pyrrolidone) as a dispersant are mixed in a mass ratio of 96.5:2.5:0.5:0.5, wherein the second lithium iron phosphate salt particles are olivine structure single crystal lithium iron phosphate, and the BET specific surface area thereof is 7 m 2 / g, Dv50 is 2.0μm, and the primary average particle size is 500nm. After mixing the above materials containing the positive electrode active material, a certain amount of N-methylpyrrolidone is added and mixed, and the first active layer slurry is prepared after being evenly dispersed.

[0194] 3. Preparation of positive electrode

[0195] After the prepared slurry is stirred evenly, the viscosity of the slurry is adjusted to 8000-20000mPa.s to prevent the prepared slurry from stratification. Then, the slurry is coated on the substrate aluminum foil through a double-sided double-cavity coating device. The coating weight of the first active layer slurry is 300mg / 1540.25cm 2 , and the second positive electrode slurry coating weight is 100mg / 1540.25cm 2 After the first active layer slurry and the second positive electrode slurry are coated, they are dried, cold pressed, cut, and sliced ​​in sequence to finally obtain the positive electrode sheet.

[0196] 4. Preparation of negative electrode

[0197] Artificial graphite as a negative electrode active material, conductive carbon black as a conductive agent, styrene-butadiene rubber (SBR) as a binder, and sodium carboxymethyl cellulose (CMC) as a thickener are mixed in a mass ratio of 95.0:1.0:2.0:2.0, deionized water is added for stirring, and after uniform dispersion, a negative electrode slurry is prepared. The negative electrode slurry is then coated on both sides of a substrate Cu foil by a double-sided coater. After both sides are completed, drying, cold pressing, slitting, and sheeting are performed to prepare a negative electrode sheet.

[0198] 5. Preparation of electrolyte

[0199] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), organic solvents ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were evenly mixed in a volume ratio of 3:7, and LiPF6 lithium salt was dissolved in the organic solvent to prepare a solution with a weight content of 12.5% ​​to obtain an electrolyte.

[0200] 6. Isolation film

[0201] Polypropylene film is used as the isolation film.

[0202] 7. Preparation of batteries

[0203] The positive electrode sheet, the separator, and the negative electrode sheet of Example 1 are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare cell, and the bare cell is welded with a pole ear, and the bare cell is placed in an aluminum shell, and baked at 80°C to remove water, and then the electrolyte is injected and sealed to obtain an uncharged battery. The uncharged battery is then subjected to the processes of static, hot and cold pressing, formation, shaping, and capacity testing in sequence to obtain the lithium-ion battery product of Example 1.

[0204] The lithium ion battery obtained in Example 1 was subjected to the performance test described below, and the results are shown in 1.

[0205] In addition, the parameters of the first lithium iron phosphate salt particles and the second lithium iron phosphate salt particles in the positive electrode sheet were changed as shown in Table 1, wherein the first lithium manganese iron phosphate salt particles (purchased from Guangdong Brunp Recycling Technology Co., Ltd., item number BP-115) were used in Example 11 and Comparative Example 2, and other than that, Examples 2-14 and Comparative Examples 1-4 were obtained in the same manner as in the examples. The cohesion, compaction density and dynamic performance of the obtained positive electrode sheets were measured respectively.

[0206] 1. Parameter determination of battery components

[0207] 1. Primary average particle size

[0208] The pole piece is cut open perpendicularly to the large surface of the pole piece by an argon ion beam to expose the cross section, which is photographed by a scanning electron microscope, and the longest diameter of the lithium iron phosphate (manganese) salt particles is statistically analyzed by the long diameter statistical method. Among them, the "primary average particle size" refers to the average value of the primary particle size of all particles, which is numerically equal to the total particle size value divided by the total number of particles. Among them, the primary particle size in the cross-section diagram refers to the longest distance connected by two points through the edge. Specifically, the total number of lithium iron phosphate (manganese) salt particles with a primary particle size greater than 50nm and the sum of the primary particle sizes of lithium iron phosphate (manganese) salt particles with a primary particle size greater than 50nm can be counted in the electron microscope scanning photo. The primary average particle size of the lithium iron phosphate (manganese) salt particles = the primary particle size of the total lithium iron phosphate (manganese) salt particles / the total number of lithium iron phosphate (manganese) salt particles. Among them, in the above particle size statistical process, particles with a primary average particle size less than or equal to 50nm are not included in the statistical range.

[0209] 2. BET specific surface area

[0210] The specific surface area was tested by gas adsorption method according to the GB / T19587-2017 test standard, as follows: lithium iron phosphate (manganese) granular salt was taken as a sample, the sample tube was immersed in liquid nitrogen at -196°C, and the adsorption amount of nitrogen on the solid surface at different pressures was measured at a relative pressure of 0.05-0.30. The monolayer adsorption amount of the sample was obtained based on the BET multilayer adsorption theory and its formula, thereby calculating the specific surface area of ​​the material.

[0211] 3. Dv50

[0212] Referring to GB / T19077.1-2016, the Dv50 value of the lithium iron phosphate (manganese) salt particles was measured using a laser particle size analyzer (Malvern Master Size 3000). In addition, the Dv10, Dv90, and Dv99 of the present application were also measured in the same manner.

[0213] 4. Carbon content

[0214] After the lithium iron phosphate (manganese) salt particles are burned in a high-frequency induction furnace, the carbon content is tested by infrared absorption method. The specific testing process is based on the standard GB / T 20123-2006 / ISO 15350:2000.

[0215] 5. Sphericity

[0216] Take the cold pressed pole piece, cut it open perpendicular to the pole piece's large surface with an Ar particle beam, expose the end face, and obtain a picture with a scanning electron microscope. Then analyze the scanning electron microscope picture of the pole piece section with image software, measure the long diameter a and short diameter b of the particle, and obtain their ratio, which is the aspect ratio of the particle.

[0217] 6. Cohesion

[0218] Select a copper plate with a smooth appearance, wipe the surface of the copper plate with dust-free paper and alcohol, and stick the double-sided tape (model: nittotape) on the copper plate. The tape width is 20mm × length is 150mm. The tape is parallel to the edge of the steel plate, and the distance from the tape to the two edges of the steel plate is equal; take the electrode to be tested, use a blade to cut a sample with a width of 25mm × length of 160mm, and stick the cut electrode sample on the double-sided tape. Align the edge of the electrode with the edge of the copper plate to ensure that the electrode and the double-sided tape fit smoothly; use a copper glue with a length of about 30mm to ensure Make sure the copper glue is parallel to the tested electrode, then use a 2kg roller to roll back and forth 3-4 times; fold the copper glue upward and fix the end of the copper plate that is not attached to the electrode with the lower clamp, and clamp the upper clamp on the paper tape and make it parallel to the copper plate; test on a computer connected to a tensile testing machine (model: INSTRON), first pre-stretch 3mm, set the rate to 10mm / min, and the displacement distance to 15mm. After obtaining the data, intercept 8-15mm data, pre-stretch 3mm for each test, repeat the test four times, and take the average value as the cohesive force.

[0219] 7. Pole compaction density

[0220] The compaction density of the film layer on one side of the pole piece = m / (V1-V2), where m represents the weight of the film layer, V1 represents the volume of the pole piece, and V2 represents the volume of the current collector. m can be obtained by subtracting the weight of the current collector from the weight of the pole piece. The product of the surface area of ​​the pole piece and the thickness of the pole piece is the volume V1 of the pole piece, and the product of the surface area of ​​the pole piece and the thickness of the current collector is V2. The thickness of the current collector and the thickness of the pole piece are obtained by measuring the thickness of the empty foil in the pole lug area with a micrometer.

[0221] 2. Determination of battery performance

[0222] 1. Battery capacity ratio when discharged from 1C to 3.2V (η value)

[0223] The preparation and testing process of the battery is as follows: 2.0000g of sample is mixed with 0.1111g of conductive carbon black and 0.1111g of PVDF (by mass ratio of 0.9:0.05:0.05), and then 2.5g of organic solvent NMP (N-methylpyrrolidone) is added, and after being fully mixed, a film with a thickness of 140μm is coated on aluminum foil, vacuum dried at 120℃ for 2h, and a round piece with a diameter of 13mm is punched using a puncher, and a sheet press is used to press the sheet at 10Mpa, and the vacuum insulation at 120℃ is carried out for 12h, and the weight of the positive electrode is weighed, wherein the loading amount of the active material is 11mg-12mg. A button cell is assembled in an argon-protected glove box, with a metal lithium sheet as the negative electrode, an electrolyte of a mixed solvent of EC (ethylene carbonate) and DMC (1,2-dimethyl carbonate) in a volume ratio of 1:1, an electrolyte LiPF6, and a diaphragm of Celgard 2400 microporous polyethylene film. Test the electrical performance of the assembled battery on a blue battery tester. In the voltage range of 2.0V to 3.75V, charge / discharge at 0.1C constant current for two weeks, and then charge / discharge at 1C constant current for two weeks to test the specific capacity. There is a constant voltage process during the charging process, the constant voltage is 3.75V, and the constant voltage cut-off current is 50uA.

[0224] A battery containing the second iron lithium salt particles as the positive electrode material is charged and discharged twice at a constant current rate of 0.1C in the voltage range of 2.0V to 3.75V, and then charged and discharged once at a constant current rate of 1C. In the charge and discharge test at a rate of 1C, the capacity value at a discharge voltage of 3.2V is extracted as C1, and the capacity value at a discharge voltage of 2.0V is extracted as C2, η=C1 / C2, wherein the charging process includes constant voltage charging, a constant voltage of 3.75V, and a constant voltage cut-off current of 50uA.

[0225] 2. Determination of kinetic performance (10% SOC DCR)

[0226] The kinetic performance of the battery in this application is specifically reflected in the measurement of the DC internal resistance (power performance).

[0227] 25℃ power performance test:

[0228] Capacity calibration: After the lithium ion batteries prepared in the embodiments and comparative examples were kept at 25°C for 2 hours, they were charged to 3.65V at a constant current of 0.33C, and then charged to 0.05C at a constant voltage of 3.65V. After the charging was completed, the tested batteries were kept at 25°C for 2 hours, and then discharged to 2.5V at a direct current of 0.33C, and the discharge capacity at room temperature was recorded as C0;

[0229] Adjust SOC (battery state of charge): After keeping the calibrated lithium-ion battery at 25°C for 2 hours, discharge it at a 1 / 3C0 discharge rate for 144 minutes to adjust the lithium-ion battery capacity to 10% SOC;

[0230] Power test: After the 10% SOC lithium-ion battery is left at 25°C for 2 hours, it is discharged at a discharge rate of 3C0 for 30 seconds under a pulse current I, and its voltage before 3C0 discharge is recorded as V1, and the voltage at the end of 30 seconds discharge is recorded as V2; the value of (V1-V2) / I is calculated, and this data can be used to characterize the power performance of the battery. The lower the value of the above dynamic performance, the better the dynamic performance of the battery.

[0231] 3. Parameters and performance in the embodiments and comparative examples

[0232] The batteries of the embodiments and comparative examples were prepared according to the above method, and various performance parameters were measured, as shown in Table 1.

[0233] Table 1

[0234]

[0235] According to Table 1, the positive electrode plates of Examples 1-14 of the present application include a first active layer and a second active layer, the first active layer includes first lithium iron phosphate salt particles and / or first lithium manganese iron phosphate salt particles, the second active layer includes second lithium iron phosphate salt particles, the primary average particle size of the second lithium iron phosphate salt particles is greater than the primary average particle size of the first lithium iron phosphate salt particles and / or the first lithium manganese iron phosphate salt particles and both are within a specific range, and the resulting secondary battery has excellent kinetic performance and excellent battery performance.

[0236] In addition, according to Table 1, among Comparative Examples 1-4 of the present application, Comparative Example 1-2 does not have one of the first active layer or the second active layer, and although Comparative Examples 3-4 have the first active layer and the second active layer, the primary average particle size of the first lithium iron phosphate salt particles and / or the first lithium manganese iron phosphate salt particles is too large or too small, and the kinetic performance of the secondary battery finally obtained is significantly lower than that of the embodiments of the present application, and cannot meet the performance requirements of the present application.

[0237] It should be noted that the present application is not limited to the embodiments described. The embodiments described are only examples, and the embodiments having substantially the same structure as the technical idea and exerting the same effects within the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the subject matter of the present application, other methods of applying various modifications that can be thought of by those skilled in the art to the embodiments and combining some of the constituent elements in the embodiments to construct the embodiments are also included in the scope of the present application.

Claims

1. A positive electrode sheet, comprising a current collector and a positive electrode active layer, wherein the positive electrode active layer is disposed on at least one side of the current collector. The positive electrode active layer includes a first active layer directly coated on the current collector, and a second active layer coated on a surface of the first active layer away from the current collector. The first active layer comprises first lithium iron phosphate salt particles and / or first lithium iron manganese phosphate salt particles, and the second active layer comprises second lithium iron phosphate salt particles. The primary average particle size of the first lithium iron phosphate salt particles and / or the first lithium manganese iron phosphate salt particles is 150nm-480nm, and the primary average particle size of the second lithium iron phosphate salt particles is 500nm-3000nm.

2. The positive electrode sheet according to claim 1, characterized in that: The cohesive force of the positive electrode plate is ≥32N / m.

3. The positive electrode sheet according to claim 1 or 2, characterized in that: The thickness of the first active layer is in the range of 80 μm to 140 μm, and the thickness of the second active layer is in the range of 8 μm to 50 μm.

4. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The BET specific surface area of ​​the first lithium iron phosphate salt particles and / or the first lithium manganese iron phosphate salt particles is 10 m 2 / g-18m 2 / g, The BET specific surface area of ​​the second lithium iron phosphate particles is 3 m 2 / g-8m 2 / g.

5. The positive electrode sheet according to any one of claims 1 to 4, characterized in that: The sphericity of the first lithium iron phosphate salt particles and / or the first lithium manganese iron phosphate salt particles is ≤1.3, and the sphericity of the second lithium iron phosphate salt particles is ≥1.

5.

6. The positive electrode sheet according to any one of claims 1 to 5, characterized in that: The molecular formula of the first lithium iron phosphate salt particle and / or the first lithium manganese iron phosphate salt particle is Li x’ M1 y’ Mn m’ Fe z’ M2 k’ PO4, wherein the M1 includes at least one of Na, K, Ca, Al, and Mg or a combination of two or more thereof, and the M2 includes one of Ni, Cu, Zn, Ti, Nb, V, Cr, and Co or a combination of two or more thereof, 0.95≤x'≤1.15, 0≤y'≤0.1, 0.1≤m'≤0.9, 0.1≤z'≤1, 0≤k'≤0.1, and the Mn content is ≤1000ppm.

7. The positive electrode sheet according to any one of claims 1 to 6, characterized in that: The molecular formula of the second lithium iron phosphate salt particle is Li m Fe x P y O j Q q , wherein Q includes at least one of Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, S, F, Cl, and Br, 0.95≤m≤1.15, 0.9≤x≤1, 0.95≤y≤1, 3.5≤j≤4, and 0<q≤0.

1.

8. The positive electrode sheet according to claim 7, wherein the Q comprises at least one of Ti, V, Mg, and Nb, Calculated based on the total weight of the second lithium iron phosphate salt particles, the content of Q is 1000ppm-10000ppm.

9. The positive electrode sheet according to claims 1 to 8, characterized in that: The second lithium iron phosphate salt particles contain carbon. The carbon content is 1.0 wt % to 2.0 wt % based on the total weight of the second lithium iron phosphate salt particles.

10. The positive electrode sheet according to claims 1 to 9, characterized in that: The first lithium iron phosphate salt particles and / or the first lithium manganese iron phosphate salt particles, and the second lithium iron phosphate salt particles are each independently single crystal particles and / or polycrystalline particles.

11. The positive electrode sheet according to any one of claims 1 to 10, characterized in that: The capacity proportion η of the second lithium iron phosphate salt particles is ≥88%, and η is defined as: a battery containing the second lithium iron phosphate salt particles as a positive electrode material is charged and discharged twice at a constant current rate of 0.1C in the voltage range of 2.0V to 3.75V, and then charged and discharged once at a constant current rate of 1C. In the charge and discharge test at the rate of 1C, the capacity value extracted when the discharge voltage is 3.2V is recorded as C1, and the capacity value extracted when the discharge voltage is 2.0V is C2, η=C1 / C2, wherein the charging process includes constant voltage charging, a constant voltage of 3.75V, and a constant voltage cut-off current of 50uA.

12. The positive electrode sheet according to any one of claims 1 to 11, characterized in that: The manufacturing process of the second lithium iron phosphate salt particles includes: providing raw materials containing at least a lithium source, an iron source, a phosphorus source, a carbon source, a carbon film-forming agent, and a modifier, and performing at least two sintering steps, wherein: The temperature of the first sintering is 500° C.-760° C., and the carbon content of the material after the first sintering is 0.01 wt %-0.79 wt %; The temperature of the second sintering is 700° C.-800° C., and the carbon content of the material after the second sintering is 0.8 wt %-2.0 wt %.

13. The positive electrode sheet according to claim 12, characterized in that: In the manufacturing process of the second lithium iron phosphate salt particles, a first crushing is performed after the first sintering, and a second crushing is performed after the second sintering, wherein: The Dv50 of the product after the first crushing is 300nm-1200nm; The Dv50 of the product after the second pulverization is 500nm-5000nm.

14. The positive electrode sheet according to any one of claims 1 to 13, characterized in that: The first active layer and the second active layer further include a conductive agent and a binder, wherein: In the first active layer, the weight ratio of the first lithium iron phosphate salt particles and / or the first lithium manganese iron phosphate salt particles: the binder: the conductive agent: the dispersant is 96-99: 0.5-3: 0.5-3: 0.5-3; In the second active layer, the weight ratio of the second lithium iron phosphate salt particles: binder: conductive agent: dispersant is 96-99: 0.5-3: 0.5-3: 0.5-3; The weight ratio of the binder in the first active layer is less than or equal to the weight ratio of the binder in the second active layer.

15. The positive electrode sheet according to claim 14, characterized in that: The conductive agent includes any one or a combination of at least two of natural graphite, artificial graphite, conductive carbon black, carbon fiber, carbon nanotube, graphene, conductive polymer or metal powder. The binder includes any one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, or polytetrafluoroethylene, or a combination of at least two of them.

16. A secondary battery, characterized in that: A positive electrode sheet according to any one of claims 1 to 15.

17. An electrical device, characterized in that: A secondary battery according to claim 16.

Citation Information

Patent Citations

  • Positive pole piece and preparation method and application thereof

    CN113036085A

  • Secondary battery pole piece, preparation method thereof and secondary battery

    CN114883521A

  • Long-circulation lithium iron phosphate thick electrode, preparation method thereof and lithium ion battery

    CN115275109A

  • Positive pole piece, lithium ion secondary battery, battery module, battery pack and electric device

    CN115842114A

  • Thick electrode and preparation method and application thereof

    CN115939300A

Cited By

  • Secondary battery, preparation method therefor, and electric device

    WO2026025952A1